From Modern to Postmodern Skyscraper Urbanism and the Rise of Historic Preservation in Sydney, Melbourne, and Perth, 1969-1988. (January 2019) - Lesh, James P.
From the late 1960s to the mid-1980s, the Australian city transitioned from modern to postmodern skyscraper urbanism. This article examines three Australian skyscrapers spanning this transition: the Mutual Life & Citizens Assurance Company (MLC) Centre in Sydney (1977), the Rialto Towers in Melbourne (1986), and the Bond Tower in Perth (1988). Despite a backlash against skyscrapers, in part brought about by heritage activists, these prominent and sizable towers were realized in historic environments. With the authorization of heritage regulators and consultants, tower builders made architectural and functional compromises for preservation, to the dissatisfaction of activists. Local and transnational forces coalesced to bring about this mode of skyscraper development, including improved construction technologies, the continued association of towers with boosterism, an intensification of economic processes, and advancements in participatory urbanism. These Australian developments exemplify the changing relationship between postmodern skyscrapers, heritage conservation, and urban planning and design.